Pengaruh Kepemimpinan Transformasional dan Budaya Kerja Terhadap Kinerja Guru Melalui Motivasi Kerja di Sekolah Dasar Gugus 01 Sugihwaras Bojonegoro - Kariyono Kariyono (Kampus Akademik Publiser, 2024)
The purpose of this study is to describe, test, and analyze the effects of Transformational Leadership and work culture on teacher performance, both directly and indirectly through teacher motivation, at Elementary School Cluster 01 Sugihwaras Bojonegoro. This research employs a quantitative approach, with a sample of 61 teachers selected using census sampling. Data collection was carried out through questionnaires and documentation, and the analysis used Partial Least Squares (PLS). The findings indicate that performance, motivation, transformational leadership, and organizational culture are all rated very high. Transformational leadership and organizational culture have a significant positive effect on teacher motivation. Organizational culture significantly impacts teacher performance, while transformational leadership does not have a direct significant effect on teacher performance. However, transformational leadership significantly affects teacher performance through motivation, and organizational culture significantly impacts teacher performance both directly and through motivation.